ANALISIS DEBIT AIR DAN MUATAN SUSPENSI PADA DAS DUA LAUT TANAH BUMBU KALIMANTAN SELATAN - Ariyani Bahar; Eko Rini Indrayatie; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2020)
Opening of forest areas for agricultural land use and other land uses can cause land damage. Soil conservation is one way to maintain soil productivity. Soil conservation can be done using the type of serai wangi (Cymbopogan nardus) which is also an economic value for producing serai wangi oil. The purpose of this study was to determine the effect of serai wangi on the physical and chemical properties of soil at the study site. The method used in this study was soil sampling using purposive sampling method in three locations, namely on alang-alang soil, lemongrass soil (aged 1 month) and fragrant lemongrass soil (age 1 year), then measuring the physical of the soil tested are soil texture, permeability, soil density, soil particle density and soil porosity, while soil chemical properties are pH, N-Total, P2O5, P-available, K2O, C-organic, Ca-dd, Mg-dd, K- dd, Na-dd, KTK, Basa Saturation. Texture measurement results in alang-alang soil, serai wangi soil (age 1 month) and serai wangi soil (1 year old) contain sand from 56.64% - 67.10%, clay at 8.74% -56.64 % and dust by 23.93% -67.63% (sandy clay clay). BD values range from 1.25 gr / cm³-1.66 gr / cm³. Soil permeability ranges from 0.45-2.77 cm / hour (rather slow). The value of soil porosity ranged from 26.63 to 55.07% (very poor-very good). Fertility status in the three treatments was assessed based on CEC ranging from 8.91-14.28 (low), base saturation ranged from 39.01-55.56 (high), P2O5 values ranged from 5.59-10.34 mg / 100g (very low-low), K-total ranges from 18.15-24.2 mg / 100g (low-medium), the organic C content ranges from 0.16-3.88% (very low-high). Based on the results of these measurements, the fertility value is declared low.Keywords: Soil Conservation; Serai wangi